Arguments that count physics, computing, and missile defense, 1949-2012 - Slayton, Rebecca 1974- (Inside technology, 2013)
In a rapidly changing world, we rely upon experts to assess the promise and risks of new technology. But how do these experts make sense of a highly uncertain future? In Arguments that Count, Rebecca Slayton offers an important new perspective. Drawing on new historical documents and interviews as well as perspectives in science and technology studies, she provides an original account of how scientists came to terms with the unprecedented threat of nuclear-armed intercontinental ballistic missiles (ICBMs). She compares how two different professional communities -- physicists and computer scientists -- constructed arguments about the risks of missile defense, and how these arguments changed over time. Slayton shows that our understanding of technological risks is shaped by disciplinary repertoires -- the codified knowledge and mathematical rules that experts use to frame new challenges. And, significantly, a new repertoire can bring long-neglected risks into clear view.